2020
DOI: 10.1038/s41598-020-62647-y
|View full text |Cite
|
Sign up to set email alerts
|

The molecular etiology of deafness and auditory performance in the postlingually deafened cochlear implantees

Abstract: Recent advances in molecular genetic testing (MGT) have improved identification of genetic aetiology of candidates for cochlear implantation (CI). However, whether genetic information increases CI outcome predictability in post-lingual deafness remains unclear. Therefore, we evaluated the outcomes of CI with respect to genetic aetiology and clinical predictors by comparing the data of study subjects; those with an identified genetic aetiology (GD group), and those without identifiable variants (GUD group). Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 45 publications
1
41
2
Order By: Relevance
“…This further speaks to the necessity of functioning neural circuits in capturing a CI's output. Moreover, another interestingly consistent finding across studies was that currently unknown mutations had significantly worse outcomes than those currently known etiologies (Lee et al, 2020). This implies that those with known mutations are more amenable to cochlear implantation than those without currently identifiable variants.…”
Section: Slc26a4* Pendrinchloride−formate Exchangermentioning
confidence: 74%
“…This further speaks to the necessity of functioning neural circuits in capturing a CI's output. Moreover, another interestingly consistent finding across studies was that currently unknown mutations had significantly worse outcomes than those currently known etiologies (Lee et al, 2020). This implies that those with known mutations are more amenable to cochlear implantation than those without currently identifiable variants.…”
Section: Slc26a4* Pendrinchloride−formate Exchangermentioning
confidence: 74%
“…Listeners who lost hearing early in life are likely to have different etiologies from those who lost hearing in adulthood. Previous studies have shown that etiology is an important, predictive factor for CI benefit (e.g., Shearer et al 2017; Shearer & Hansen 2019; Lee et al 2020). In addition, Jahn & Arenberg (2020) recently showed that how well the electrical stimulation delivered by individual CI electrodes could activate target AN fibers was different between young CI users who were deafened and implanted during childhood and older CI users who were deafened and implanted as adults.…”
Section: Discussionmentioning
confidence: 99%
“…The auditory outcome after CI was very good in most patients with DFNA36; a poor outcome was observed only in a patient who underwent CI after 20 years of deafness (online suppl. Table 4) [Makishima et al, 2004;Lee et al, 2020]. A correlation between deafness duration and auditory outcome was suggested; however, good results in speech perception were observed in 2 adult members of a North American Caucasian family with DFNA36 who underwent CI after 2 decade of deafness [Makishima et al, 2004].…”
Section: Discussion/conclusionmentioning
confidence: 99%